A Usability Study of an Educational Groupware System: Supporting Awareness for Collaboration. (April 2014) - Tang, Tiffany Y.; Winoto, Pinata; Leung, Hareton
A number of research studies have focused on the usability of groupware in supporting collaborative work. Unfortunately, our understanding of their impact on collaborative learning is still limited due to a lack of attention on this issue. The majority of educators and designers in Computer Supported Collaborative Learning (CSCL) expect interactions and collaborations to come naturally. As a result, they are focused on providing a wide variety of interaction opportunities for both learners and educators through producing versatile tools in educational groupware systems, but they ignore the most important factor—whether these features are valuable at all. To bridge this gap, in this article, we describe our experiences with a loosely-coupled collaborative software called GroupScribbles, and explore its potential and challenges in supporting cooperation and coordination among learners. Our study suggests versatility is not of singular importance in an educational groupware tool. Rather, how it can provide a seamless and focused distributed learning environment determines the overall pedagogical appropriateness of the software in CSCL. The learning environment, although distributed and fragmented, should be capable of linking learners, their activities and their meta-cognitive problem solving skills cohesively so as to continuously construct a relatively compact learning space where coordination and collaboration can be effective and efficient.